Voss, du roman de Patrick White au livret de David Malouf : simple adaptation ou transformation de l’imaginaire national ? - Anne Le Guellec-Minel (Revue LISA)
When a couple of years before Australia’s Bicentenary celebrations, David Malouf accepted the commission from Opera Australia, the Sydney Opera company, to adapt Patrick White’s novel Voss for the operatic stage, he was certainly aware that this meant participating in the Establishment’s efforts to promote a culturally exalted Australian identity on the European model. When the opera was premiered in 1986, the libretto was praised both by the critics and the public for its success in making use of the dramatic potential of the novel and, beyond that, in bringing out the musical possibilities of a style which had often been described as difficult and obscure. This article first undertakes to analyse a few aspects of Malouf’s generic rewriting of the source text, which suggest that insofar as the opera was designed as a monumental celebration to Australian achievement, the libretto does seem to betray, to a certain extent, the novel’s criticism of heroic posturing and complacent patriotism, and to collaborate in the institutional recuperation of what remains a controversial work. However, a closer study of the way in which Malouf writes his own homoerotic poetry into White’s narrative reveals that it subtly contributes to maintaining a truly “post-colonial” ambivalence within the apparent conventionality of the national celebration.